Flight - Vinson, Ben. author. aut Link
X, 204 p.
Keywords: Virgil Richardson blazed his own unique trail through the twentieth century: a co-founder of Harlem's American Negro Theater, 1930s radio personality, World War II pilot, and expatriate for most of his life. In Flight, this remarkable man tells his story in his own vivid words. Educated in Texas, Richardson set out for New York City in 1938 to build a career on the stage. Just when he was on the brink of success as an actor, World War II broke out and he was drafted into the army. After overcoming numerous obstacles, Richardson became a Tuskegee cadet in 1943, and later saw action flying over the battlefields of Europe. Upon returning to the racially divided U.S., he decided to move to Mexico, where he encountered a society quite different from the one he had left behind. Compellingly told and historically fascinating, this is the story of a determined individual unwilling to accept the limited options of Jim Crow America.